2017
DOI: 10.1111/apt.13988
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with villus atrophy in symptomatic coeliac disease patients on a gluten‐free diet

Abstract: Of 1345 symptomatic patients, 511 (38%, 95% CI, 35-41%) were found to have active coeliac disease with persistent villus atrophy, defined as average villus height to crypt depth ratio ≤2.0. On multivariable analysis, older age (OR, 5.1 for ≥70 vs. 18-29 years, 95% CI, 2.5-10.4) was a risk factor while longer duration on gluten-free diet was protective (OR, 0.37, 95% CI, 0.24-0.55 for 4-5.9 vs. 1-1.9 years). Villus atrophy was associated with use of proton-pump inhibitors (PPIs; OR, 1.6, 95% CI, 1.1-2.3), non-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 35 publications
6
69
1
1
Order By: Relevance
“…Under‐reporting the severity of mucosal injury in follow‐up biopsies is concerning for patients and treating physicians, but in this study was rectified by re‐cutting biopsies with poorly orientated tissue sections. A further limitation of our findings might be that we did not consider potential drug‐induced enteropathy to occur in our study subjects, for example subjects using Olmesartan, proton pump inhibitors, nonsteroidal anti‐inflammatory drugs or selective serotonin reuptake inhibitors …”
Section: Discussionmentioning
confidence: 99%
“…Under‐reporting the severity of mucosal injury in follow‐up biopsies is concerning for patients and treating physicians, but in this study was rectified by re‐cutting biopsies with poorly orientated tissue sections. A further limitation of our findings might be that we did not consider potential drug‐induced enteropathy to occur in our study subjects, for example subjects using Olmesartan, proton pump inhibitors, nonsteroidal anti‐inflammatory drugs or selective serotonin reuptake inhibitors …”
Section: Discussionmentioning
confidence: 99%
“…The findings of our study are limited to the day of a substantial gluten exposure when nausea predominates and are informative of acute symptoms within hours of gluten ingestion. Duodenal injury related to chronic gluten exposure is found in many patients with coeliac disease on a gluten‐free diet . Therefore, IBS‐like symptoms being common in coeliac disease may be a nonspecific effect of mucosal inflammation rather than directly linked to gluten‐mediated immune activation .…”
Section: Discussionmentioning
confidence: 99%
“…The literature on coeliac disease and depression and anxiety is abundant, but so far we are unaware of any studies exploring the association with mucosal healing. One prior study of coeliac disease participants in a clinical trial found that antidepressant use was associated with an increased prevalence of persistent villous atrophy, though depressive symptoms were not measured and clinical trial participants may not be representative of the general coeliac population …”
Section: Discussionmentioning
confidence: 99%